2021
DOI: 10.1177/08971900211021269
|View full text |Cite
|
Sign up to set email alerts
|

Publication of Pharmacy Residency Research: A 12-Year Cohort From an Academic Medical Center

Abstract: Background: Pharmacy residency programs provide research training experiences to residents, and publication is considered an indicator of high-quality research experiences. Objective: This study described attributes of pharmacy residents, residency programs, and residency major research projects and their associations with the outcome of publication in a peer-reviewed journal. Methods: Pharmacy residents who graduated from one academic medical center between 2001 and 2012 were invited to participate via an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Pharmacy residency programs nationwide have struggled to provide effective research and scholarship learning experiences, fueling the chasm between the expectations placed upon early‐career clinical pharmacists and the skills provided by their training 5,7,12,14,21,22 . While the benefits of research training in pharmacy residency extend far beyond those of publication, the poor publication rates of pharmacy resident research projects have likely come at the costs of reduced knowledge dissemination and stunted early‐career scholarly productivity 2,3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacy residency programs nationwide have struggled to provide effective research and scholarship learning experiences, fueling the chasm between the expectations placed upon early‐career clinical pharmacists and the skills provided by their training 5,7,12,14,21,22 . While the benefits of research training in pharmacy residency extend far beyond those of publication, the poor publication rates of pharmacy resident research projects have likely come at the costs of reduced knowledge dissemination and stunted early‐career scholarly productivity 2,3 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been recommended that community hospital programs consider partnering with academic medical centers to provide similar learning experiences 2 . Yet, only about a quarter of pharmacy residents at well‐resourced academic medical centers appear to subsequently publish their research, 12,13 and this rate appears to be only 1.8% to 16% nationwide 5,14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the value of pharmacy students, residents, and fellows conducting research. [6][7][8][9][10][11] However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%
“…Some pharmacy students, residents, or fellows pursue a career in academia where they are typically required to engage in scholarly activities. Studies have shown the value of pharmacy students, residents, and fellows conducting research 6–11 . However, when pharmacy students, residents, fellows, faculty, or other early career pharmacists do engage in research, it is often their first time, or one of their first times, and they may therefore be unprepared.…”
Section: Introductionmentioning
confidence: 99%